Highly efficient electrochemical reduction of carbon dioxide to formate on Sn modified Bi2O3 heterostructure. Issue 40 (6th October 2021) - Wu, Doufeng; Chen, Pengzuo; Feng, Dongmei; Song, Jiajia; Tong, Yun
Abstract : A simple chemical strategy is designed to prepare Sn modified Bi2 O3 materials with controllable doping contents. The optimal SnM –Bi2 O3 heterostructure exhibits a superior electrochemical performance towards CO2 reduction to formate production. Abstract : In this work, Sn species are deposited onto the surface of a Bi2 O3 material by a facile disproportionated reaction and the prepared catalyst shows a superior electrocatalytic performance towards CO2 reduction. The deposition of Sn atoms can donate electrons to the Bi2 O3 material and increase its electrical conductivity. The SnM –Bi2 O3 catalyst with the optimal Sn content delivers a high faradaic efficiency of 95.8% at −1.0 V for formate production. In addition, the partial current density of formate can reach 41.8 mA cm −2 . The SnM –Bi2 O3 catalyst also exhibits superior stability towards long-term electrolysis. The modification of Sn species not only helps to stabilize the reaction intermediate but also inhibits the hydrogen evolution reaction (HER) pathway, achieving the synergetic enhancement of catalytic activity.